The interdependance of petroleum price between selected Middle East Countries and Malaysia: analysis based on quantitative indices / Nasreen Athirah Mohd Aludin and Mohamad Nazarin Mohamad Napi - Mohd Aludin, Nasreen Athirah; Mohamad Napi, Mohamad Nazarin (Faculty of Business and Management, 2016)
The study examined the interdependence of oil price between the selected Middle East countries and Malaysia with quantitative indices. The methodology is panel regression method approach. The dependent variable of this study is the Oil Price (OP), meanwhile the independent variables used for analysis were Foreign Exchange Rate (FER), Inflation Rate (IR), Gross Domestic Product (GDP), Import of Fuel (IF), and Export of Fuel (EF) in Saudi Arabia, United Arab Emirates, Kuwait, Qatar, Iran, and Malaysia. These variables were considered appropriate indicators of oil price responses. The main tool of analysis was a random regression model which examines the relationship between oil prices and the variables in selected countries from 1984 until 2013. Data on the variables were used to estimate parameters of the model through the Panel Regression Random Effect Model. Estimates of model parameters were evaluated based on relevant statistics from the regression. The results show positive relationship exists between FER and EF with the OP. Meanwhile, IR has negative relationship with the OP. Another two variables which are GDP and IF shows no significant relationship with the OP. However, the overall effect showed increase in the variables increase the price of oil in all countries selected.